Social critique in J.D. Salinger’s Catcher in the Rye - Hameed Mankhi, Azhar (Opción, 2019)
The aim of this research is to show the mental reasons behind the desires of the hero in Salinger’s Catcher in the Rye (1950) to refuse the adult world in their societies via comparative qualitative research method. The author attempts to show how the post -war era affects the youth generation. A new countercultural voice emerged which refused all the values and standards of their parents. The result of this conflict is isolation and separation. In conclusion, Holden does not only act as the spokesman for all the youth but he succeeds in creating a character that represents all youth.